Domain Examination of Chaos Logistics Function As A Key Generator in Cryptography - Alz Danny Wowor; Vania Beatrice Liwandouw (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The use of logistics functions as a random number generator in a cryptography algorithm is capable of accommodating the diffusion properties of the Shannon principle. The problem that occurs is initialization x was static and was not affected by changes in the key, so that the algorithm will generate a random number that is always the same. This study design three schemes that can providing the ﬂexibility of the input keys in conducting the examination of the value of the domain logistics function. The results of each schemes do not show a pattern that is directly proportional or inverse with the value of x0 and relative error x and successfully fulﬁll the properties of the butterﬂy effect. Thus, the existence of logistics functions in generating chaos numbers can be accommodated based on key inputs. In addition, the resulting random numbers are distributed evenly over the chaos range, thus reinforcing the algorithm when used as a key in cryptography.